Kynurenic acid attenuates pro-inflammatory reactions in lipopolysaccharide-stimulated endothelial cells through the PPARδ/HO-1-dependent pathway. (15th September 2019) - Lee, Taeseung; Park, Hyung Sub; Jeong, Ji Hoon; Jung, Tae Woo
Abstract: Kynurenic acid (KA) regulates energy homeostasis and alleviates inflammation in adipose tissue but how KA affects the atherosclerotic response in HUVECs remains unclear. We evaluated the effects of KA on lipopolysaccharide (LPS)-induced inflammation and apoptosis in HUVECs. KA enhanced peroxisome proliferator-activated receptor delta (PPARδ) expression in HUVECs and THP-1 cells and suppressed LPS-induced atherosclerotic responses through PPARδ-mediated signaling. Moreover, KA treatment mitigated LPS-induced phosphorylation of nuclear factor kappa B and pro-inflammatory cytokine release in HUVECs and THP-1 cells, and down-regulated adhesion molecules in HUVECs and adhesion of THP-1 cells to HUVECs following LPS treatment. KA treatment decreased LPS-induced inflammation and apoptosis, and also promoted heme oxygenase (HO)-1 expression, which suppresses inflammation in HUVECs. Suppression of PPARδ or HO-1 expression markedly mitigated the effects of KA on atherosclerotic responses in HUVECs. Thus, KA attenuates LPS-induced atherosclerotic responses by suppressing inflammation via the PPARδ/HO-1-dependent pathway. Graphical abstract: Image 1 Highlights: Kynurenic acid (KA) suppresses inflammation and apoptosis in LPS-treated HUVEC. KA ameliorates inflammation in THP-1 cells. KA enhances PPARδ and HO-1 expression in both cell types. PPARδ and HO-1 contribute to the effects of KA on inflammation and apoptosis in HUVEC.